A Long‐Lived Sharp Disruption on the Lower Clouds of Venus. Issue 11 (27th May 2020) - Peralta, J.; Navarro, T.; Vun, C. W.; Sánchez‐Lavega, A.; McGouldrick, K.; Horinouchi, T.; Imamura, T.; Hueso, R.; Boyd, J. P.; Schubert, G.; Kouyama, T.; Satoh, T.; et al.
Abstract: Planetary‐scale waves are thought to play a role in powering the yet unexplained atmospheric superrotation of Venus. Puzzlingly, while Kelvin, Rossby, and stationary waves manifest at the upper clouds (65–70 km), no planetary‐scale waves or stationary patterns have been reported in the intervening level of the lower clouds (48–55 km), although the latter are probably Lee waves. Using observations by the Akatsuki orbiter and ground‐based telescopes, we show that the lower clouds follow a regular cycle punctuated between 30°N and 40°S by a sharp discontinuity or disruption with potential implications to Venus's general circulation and thermal structure. This disruption exhibits a westward rotation period of ∼4.9 days faster than winds at this level (∼6‐day period), alters clouds' properties and aerosols, and remains coherent during weeks. Past observations reveal its recurrent nature since at least 1983, and numerical simulations show that a nonlinear Kelvin wave reproduces many of its properties. Plain Language Summary: One of the biggest mysteries of Venus is its atmospheric superrotation that allows the atmosphere to rotate 60 times faster than the solid planet. Atmospheric waves are among one of the possible mechanisms thought to feed this superrotation by pushing energy to different locations of the atmosphere. In fact, the upper clouds of Venus located at 65–70 km exhibit varied giant waves, like the so‐called Y feature or the more recently discovered bow‐shaped wave that keeps "stationary" over Aphrodite mountains. In contrast, these planetary‐scale waves are missing at the deeper lower clouds (48–55 km). This is especially puzzling in the case of the stationary waves since the lower clouds are located between the upper clouds and the surface, where they are thought to be generated. Thanks to the high‐quality observations of Venus from JAXA's space mission Akatsuki and NASA's IRTF telescope, we discovered at the lower clouds an intriguing sharp discontinuity that propagates to the west faster than the winds while altering the clouds' properties and suffering little distortions during weeks. A reanalysis of past observations revealed that this is a recurrent phenomenon that has gone unnoticed since at least the year 1983. Numerical simulations evidence that an atmospheric wave generated below the clouds and probably pumping energy to the upper clouds can explain many of its properties. Key Points: Discovery of an equatorial cloud discontinuity at the middle and lower clouds of Venus, where no planetary wave had been found before This disruption propagates to the West faster than the winds, keeps coherent for weeks, and alters clouds' properties and aerosols Past observations confirm its existence since 1983; numerical simulations suggest a physical origin as a nonlinear Kelvin wave